The Effect of Justice Expenditures on the Crime Rate: The Case of Colombia during the 20th Century - GAITÁN-GUERRERO, Loly Aylú (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
This study presents an empirical and quantitative study of the causes of variation in the crime rate at the municipal level. To this end, using an historical perspective, the primary sources of municipal data used were the homicide rate in 1962, the budget expenditures intended for the Department of Justice from 1918 to 1935 and the National Population Census from 1918 to 1935. The result was a strong negative relationship between crime rates in 1962 and the allocation of justice expenditures from 1918 to 1935, among other variables. This result means that, in the long-term, the variation in the homicide rate resulted from larger or smaller expenditure allocations to the justice sector at the municipal level.